2021
DOI: 10.1186/s13068-020-01863-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of 10-methyl branched fatty acids in yeast

Abstract: Background Despite the environmental value of biobased lubricants, they account for less than 2% of global lubricant use due to poor thermo-oxidative stability arising from the presence of unsaturated double bonds. Methyl branched fatty acids (BFAs), particularly those with branching near the acyl-chain mid-point, are a high-performance alternative to existing vegetable oils because of their low melting temperature and full saturation. Results We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Recent studies have indicated that Actinomycetes express a three-reaction pathway that metabolically links these two fatty acids. Specifically, a Δ-9 acyl-CoA desaturase (Tfu_0413) ( Lykidis et al, 2007 ) can generate monounsaturated fatty acids, which are substrates for BfaB (Tfu_2160) and BfaA (Tfu_2161) enzymes, which transform the monounsaturated acyl-CoA to 10-methylene BCFA and to 10-methyl BCFA, respectively ( Blitzblau et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have indicated that Actinomycetes express a three-reaction pathway that metabolically links these two fatty acids. Specifically, a Δ-9 acyl-CoA desaturase (Tfu_0413) ( Lykidis et al, 2007 ) can generate monounsaturated fatty acids, which are substrates for BfaB (Tfu_2160) and BfaA (Tfu_2161) enzymes, which transform the monounsaturated acyl-CoA to 10-methylene BCFA and to 10-methyl BCFA, respectively ( Blitzblau et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the T. fusca genome features enzymes capable of modifying fatty acids following their assembly by the FAS system. These include an acyl-CoA desaturase to produce unsaturated fatty acids, which are substrates for a methylase and reductase needed to generate 10-methyl BCFAs ( Blitzblau et al, 2021 ). These three enzymes, in addition to the flexibility of the FAS system to use an assortment of α-carboxyl acyl-CoAs, indicate that T. fusca possesses the metabolic machinery to convert plant biomass to a wide array of fatty acids that have applications as biorenewable products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We saw an increase in the total PL fraction in that strain, which could be used for metabolic engineering applications that use PLs as a precursor, e.g. branched fatty acids production [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent technological advancements in DNA synthesis, assembly, genome editing, and computational approaches have substantially improved FA production and the production of other compounds in microbes. In E. coli and yeast, these advancements have led to the production of artemisinic acid [52], resveratrol [53], FAs [25,[54][55][56][57][58], and alkanes [45]. Recently, by engineering synthetic metabolic pathways, the engineered strain of Rhodococcus opacus was able to produce higher FAs as well as long-chain hydrocarbons as compared to the wild-type [16].…”
Section: The Importance Of Fa Production By Microbesmentioning
confidence: 99%